THE CHILD'S VIEW OF THE TERRITORY: PERSPECTIVES FOR CHILD DEVELOPMENT - Fernanda Anjos de Oliveira; Claudia Nery Teixeira Palombo; Melissa Almeida Silva; Clariana Vitória Ramos de Oliveira (Cogitare Enfermagem)
Objective: to understand children's perspective on the territory in which they live.